2020
DOI: 10.1111/rda.13853
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin can improve viability and functional integrity of cooled and frozen/thawed rabbit spermatozoa

Abstract: Melatonin is known to protect sperm against freezing‐inflicted damage in different domestic species. The aim of the study was to evaluate the effect of supplementation of semen extender with melatonin on the quality and DNA integrity of cooled and frozen/thawed rabbit spermatozoa. We also investigated whether the addition of melatonin to the semen extender could improve the fertility of rabbit does artificially inseminated with frozen/thawed semen. Semen samples collected from eight rabbit bucks were pooled an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 63 publications
(83 reference statements)
2
17
1
Order By: Relevance
“…In addition, the highest degree of progressive motility corresponded to this same concentration of MT; however, no significant difference was observed in the frozen control group. The results of this part of the study are consistent with those of a study by Fadl et al [ 18 ] that found that concentrations of 1 mM MT corresponded to the highest degree of progressive motility compared to other doses as well as the control group. In addition, the present study showed that adding Se to the extender did not significantly improve rat sperm motility after thawing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the highest degree of progressive motility corresponded to this same concentration of MT; however, no significant difference was observed in the frozen control group. The results of this part of the study are consistent with those of a study by Fadl et al [ 18 ] that found that concentrations of 1 mM MT corresponded to the highest degree of progressive motility compared to other doses as well as the control group. In addition, the present study showed that adding Se to the extender did not significantly improve rat sperm motility after thawing.…”
Section: Discussionsupporting
confidence: 92%
“…Semen samples with a concentration of 20×10 6 sperm/mL to 30×10 6 sperm/mL were diluted in a TL-HEPES extender solution, and the semen of each rat was divided into six groups, with four groups containing MT and Se at concentrations of 0.5 mM and 1 mM and two groups containing no added material, which were used as fresh and cryopreservation control groups, respectively [ 18 , 19 ]. The samples were cooled to 4°C and equilibrated at this temperature for 2 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Melatonin, as an antioxidant, anti-apoptotic and free-radical scavenger, is involved in cell protection [ 20 ]. In recent years, the protective effect of adding melatonin to the freezing medium has been tested on sperm viability after thawing [ 38 40 ]. The results demonstrated that melatonin at a concentration of 100 μM increased the viability of frozen–thawed SSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu and colleague investigated the effects of supplementation of amin E analogue [ 64 ], cysteine [ 65 ], glutamine [ 66 ], trehalose [ 67 ] and melatonin [ 68 ], and revealed that supplementation of these antioxidative agents in Tris-citrate-glucose extender decreased ROS levels and improved the quality of frozen–thawed rabbit sperms. Fadl et al confirmed 1.0 mM melatonin improved the motility, viability, membrane and acrosome integrities, and DNA integrity of frozen–thawed rabbit sperms in different extender (INRA-82) [ 69 ] Additionally, curcumin and curcumin nanoparticles were confirmed to improve the post-thawed quality of rabbit sperms via redox signaling and reduce the apoptosis process [ 70 ]. On the other hand, Maya-Soriano et al reported that supplementation of bovine serum albumin, retinol and retinyl in the sperm freezing extender has no beneficial effect on the viability, mortality, progressivity, and acrosome and morphological integrity of frozen–thawed rabbit sperms at the concentrations they tested [ 71 ].…”
Section: Effects Of Supplementsmentioning
confidence: 99%